PENGARUH IKLIM SEKOLAH DAN DISIPLIN TERHADAP KINERJA GURU MEDIASI MOTIVASI - Irianti, Endang (Students Journal of Economic and Management, 2012)
Purpose of this research is to test and description of influence: 1) school climate to motivation of job, 2) job discipline to motivation of job, 3) motivation of job to teacher performance, 4) school climate to teacher performance, and 5) job discipline to teacher performance.This research executed in TK Wilayah Kecamatan Tambakromo Kabupaten Pati, teacher sample TK 101 teacher by using nonprobability sampling. Collecting propagates questionnaire, applies scale model equate Likert with modification 7 scale. Analytical technique applied is descriptive, linear partial correlation and regression at level significance 5%.Result of descriptive analysis indicates that responder comments about statement of questionnaire propagated about teacher performance, school climate, teacher job discipline and motivation of teacher job average of responder answers "agrees". Model linear regression equation of a line 1 is Y1 = 0,681X1 + 0,322X2. At calculation tee test and Test F is got by result there are influence in simulate and significant between school climates and job discipline to motivation of job, with correlation coefficient R 0,923 mean there is unidirectional / positive and strong relationship between school climates and teacher job discipline to motivation of job or on the contrary. Model linear regression equation of a line 2 is Y2 = 0,054X1 - 0,036X2 + 0,973Y1. Bases on calculation tee test and Test F is got by result there are influence in simulate and significant between school climates, job discipline and motivation of job to teacher performance, with correlation coefficient R 0,918 mean there is a real unidirectional / positive and strong relationship between school climates, teacher job discipline and motivation of job to teacher performance or on the contrary. Based on calculation data analysis through test mediation it is concluded that motivation of job mediation can (influential indirect) at school climate variable and job discipline and both the independent variables influential direct to teacher performance. Keyword : teacher performance, school climate, job discipline and motivation of job.